The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/apa.14799
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, pain and analgesic use in school‐age children

Abstract: Aim: The aim of this study was to examine whether the self-reported use of analgesics is associated with being a victim of bullying.Methods: This cross-sectional, school-based survey included all students in grades 6 (11 years old), 8 (13 years old) and 10 (15 years old) in Iceland (response rate: 84%; n = 11 018). The students filled out an anonymous standardised questionnaire: the Icelandic Contribution to the International Health Behavior in School-Aged Children (HBSC) Study.Results: Being bullied was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The regulations and requirements concerning human subject research, as laid out by the Data Protection Authority in Iceland (Personuvernd, 2013), were followed. Methodological details are described elsewhere (Garmy et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulations and requirements concerning human subject research, as laid out by the Data Protection Authority in Iceland (Personuvernd, 2013), were followed. Methodological details are described elsewhere (Garmy et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Bullying is a pervasive peer relationship problem with psychological, social, and academic consequences (Annerback, Sahlqvist, & Wingren, 2014;Barzilay et al, 2017;Fahy et al, 2016;Landstedt & Persson, 2014;Waasdorp & Bradshaw, 2015). Studies have also indicated a possible association between bullying and physical symptoms, such as pain (Fridh, Kohler, Moden, Lindstrom, & Rosvall, 2018;Gini, Pozzoli, Lenzi, & Vieno, 2014) and the use of analgesics (Garmy, Hansson, Vilhjalmsson, & Kristjansdottir, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, an analysis of the international HBSC data revealed that bullying actually has a stronger negative effect on life satisfaction of individuals in schools and countries where bullying is less frequent (Arnarsson & Bjarnason, 2018). In Iceland, victims of bullying report poorer relations with their parents and are less likely to report having a best friend (Arnarsson & Bjarnason, 2009), report more physical and psychological symptoms (Garmy, Hansson, Vilhjálmsson, & Kristjánsdóttir, 2019a; Hansson, Garmy, Vilhjálmsson, & Kristjánsdóttir, 2020), use more pain medication controlling for self‐reported pain (Garmy, Hansson, Vilhjálmsson, & Kristjánsdóttir, 2019b), and are more likely to have attempted suicide (Arnarsson, Malmquist, & Bjarnason, 2017).…”
Section: Iceland As a Setting Of Studymentioning
confidence: 99%
“…An Icelandic school‐based survey study of 10 390 adolescents aged 11, 13 and 15 years showed that the use of pain medication was significantly higher among students who were bullied . The difference remained, even when the data were controlled for the amount of reported pain, age, gender and socioeconomic status.…”
Section: Bullied Students Were More Likely To Use Pain Medicationmentioning
confidence: 99%